Fungsi Lurah dalam Meningkatkan Pembangunan dan Kesejahteraan Masyarakat di Kelurahan Prailiu dan Kelurahan Kambaniru Kecamatan Kambera Kabupaten Sumba Timur - Kalaway, Umbu Rizky; Yohanes, Saryono; Montero, Josef Mario (Law Faculty, Nusa Cendana University, 2023)
The institution of the political district administered by the village chief plays the function of implementation of program and activities of community empowerment and services, peace and policing construction, infrastructure and public facilities keeping, and cultivate and facilitate the economic development increasing of the community in the village. This study is aimed to analyze the implementation and the impediment factors of the implementation of the role of the village chief in development and community welfare enhancement in Prailiu and Kambaniru Village of Kambera Subdistrict of East Sumba Regency. This was an empirical judicial research with sociological and conceptual approach. The data processing technique used were editting, coding, clarification and tabulation, and analyzed empirically appropriate to the gained data and with law theory, principle and norm persistent observance. The results revealed that the chief of the Prailiu and Kambaniru village of Kambera Subdistrict of East Sumba Regency have performed the development and community welfare enhancement role eventhough not optimal yet, which were (1) utilities and infrastructures development enhancing in the form of market place and the aid of rowing boat and trawl, piggies, goat and hen livestocks, motorcycle workshop equipments for the community, high road, footpath lane and drainage ditch construction, (2) of security indicator were coordination with the harmonious neighboring chief to respon and follow-up the commmunity complaints, (3) of health indicator were social and working aids channelization, and third party cooperation, (4) of human resources enhancing indicator were community empowerment, social organization and community self-supporting mutual assistance building, and (5) of environment contamination prevention indicator were aid granting of kiosks and goods-selling basket building, market place and drainage ditch construction. The impediment factors of the role implementation were (1) public utilities and infrastructures still depended to the fund and budget availability, the poor condition of the high road and footpath lane, the market location less strategic, (2) institution apparatus slow-moving services given caused by lack of coordination, (3) socialization minimity, and (4) budget availability minimity.Researcher suggests that the concerned stake holders which are the chief and the all human resources apparatus set of the Prailiu and Kambaniru village institution should maintain even enhancing the community services performance and pay more attention to and solution finding efforts of the impediment factors of the village chief implementation in order to generate the community active participation in the village development for the reaching of the development goals that is to social welfare